An Integrated Software Development Environment for Web Applications - Kang, Byeongdo (Software Engineering Research and Applications, 2006)
In recent years, the World Wide Web has become an ideal platform for developing Internet applications. World Wide Web service and application engineering is a complex task. Many web applications at present are large-scale and involve hundreds or thousands of web pages and sophisticated interactions with users and databases. Thus, improving the quality of web applications and reducing development costs are important challenges for the Internet industry. One way to resolve the difficulty is to provide web application developers with an integrated development environment. In this paper, I propose an efficient methodology and development environment for web application programs. This environment includes a design model to represent data and navigational structure, a modeling language for the notation technique of the design model, and a process model to define development stages.